2019
DOI: 10.1007/s40095-019-0305-0
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of wood pellets mixed with torrefied rice straw as a biomass fuel

Abstract: Utilization of rice straw as an alternative fuel source to fossil fuel has been considered. However, properties such as water content, low heating value, less grindability, high bulk density, and high ash content are problems in such a biomass fuel supply chain. This study attempted to produce wood pellets mixed with torrefied rice straw (WPTRS) to solve the problems related to using rice straw as fuel. For that, preferred torrefaction conditions, such as torrefaction temperature and holding time, were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Consistently, significant attention has been given to the torrefaction process, particularly as a pre-treatment. Feedstock torrefaction was very effective in improving pellet parameters, mostly those linked with energetic efficiency [108] but also mechanical characteristics [109,110]. Pellets produced from torrefied biomass were of a high quality according to ISO standards for industrial pellets when this treatment was applied to pruning residual biomass of olives and almonds.…”
Section: Pre-and Post-treatmentsmentioning
confidence: 99%
“…Consistently, significant attention has been given to the torrefaction process, particularly as a pre-treatment. Feedstock torrefaction was very effective in improving pellet parameters, mostly those linked with energetic efficiency [108] but also mechanical characteristics [109,110]. Pellets produced from torrefied biomass were of a high quality according to ISO standards for industrial pellets when this treatment was applied to pruning residual biomass of olives and almonds.…”
Section: Pre-and Post-treatmentsmentioning
confidence: 99%
“…Kizuka et al observed that the mixing of torrefied RS at 280 °C with wood biomass pellets at a ratio of 10% RS to the pellets generated resulted in a lower heating value (LHV) of 16.5 MJ/kg, which is higher than the LHV of wood [ 102 ]. Conversely, they also found a higher energy loss at a 280 °C torrefied temperature, whereas a torrefaction temperature of over 220 °C was needed to improve the grindability of RS.…”
Section: Pre-treatment Of Rice Residuesmentioning
confidence: 99%
“…Moreover, the LHV decreased as the mixing ratio of torrefied rice straw (TRS) to wood increased. The adaptation of torrefaction pre-treatment prior to the pelletization process will achieve wider application of the final produced pellets and contribute additional regional economic benefits [ 102 ]. Another study by Homdoung et al [ 103 ] proved that the average bulk density and durability of torrefied RH pellets were 1112 kgm −3 and 90.6%, respectively.…”
Section: Pre-treatment Of Rice Residuesmentioning
confidence: 99%
“…in direct contact with the feedstock. In the second, indirect mode heating application separates the heating media from the biomass by a conductive barrier such as metal walls [39,47]. Biomass can also be heated by microwaves at a frequency of 2.4 GHz.…”
Section: Torrefaction Reactors and Technologiesmentioning
confidence: 99%